Modern Chinese and Japanese garden as a symbol of national identity in the context of globalism - Ding, Yang; Semykina, Olena; Mykhailenko, Andriy; Ushakova, Olga; Khliupin, Oleksandr (Landscape Architecture and Art, 2021)
The article considers examples of modern gardens and parks with elements of Chinese and Japanese landscape design, analyzes the degree of their similarity with historic gardens. A comparative analysis of historic gardens and modern gardens and parks is carried out in order to prove which elements of traditional oriental landscape design are cited the most. A set of elements that embody national identity in modern Chinese and Japanese gardens is argued. It is shown how, over time, including under the direct influence of multiculturalism and in connection with the typification of pavilions for mass construction, the concentrated national features of eastern gardens were gradually smoothed out. As the most recognizable elements of modern Chinese gardens, pavilions, sculpture, compositions of stones, Japanese gardens – gates-torii, pagodas, compositions of boulders, "dry gardens", landscaping with sakura, coniferous trees, and Japanese maples were identified. Compared to Chinese gardens, in a modern Japanese garden outside of Japan there may be no buildings at all or their number is minimal, and the natural environment itself is more natural. On the contrary, the Chinese garden outside of China showcases the art of landscape design and the craftsmanship of man-made landscape paintings.